2011
DOI: 10.4269/ajtmh.2011.10-0325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Areas for Visceral Leishmaniasis in Teresina, Piaui State, Brazil

Abstract: This study used spatial analysis to identify areas at greatest risk of visceral leishmaniasis (VL) in the urban area of Teresina, Brazil during 2001–2006. The results from kernel ratios showed that peripheral census tracts were the most heavily affected. Local spatial analysis showed that in the beginning of the study period local clusters of high incidence of VL were mostly located in the southern and northeastern parts of the city, but in subsequent years those clusters also appeared in the northern region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
3
42
0
6
Order By: Relevance
“…Numerous studies have demonstrated a risk for ZVL based on the presence of dogs within the household, housing types (mud-walled housing compared to concrete or brick housing), education level, income, and disease knowledge (271,272,327,328). Clinical ZVL has also been associated with poor nutrition (328).…”
Section: Fig 10mentioning
confidence: 99%
“…Numerous studies have demonstrated a risk for ZVL based on the presence of dogs within the household, housing types (mud-walled housing compared to concrete or brick housing), education level, income, and disease knowledge (271,272,327,328). Clinical ZVL has also been associated with poor nutrition (328).…”
Section: Fig 10mentioning
confidence: 99%
“…The evaluation of endemic diseases from the perspective of various elements involved in the transmission cycle, such as environmental and social determinants of the disease, has been the focus of some studies employing geoprocessing techniques 8,9,10,11,12 . Geoprocessing tools, especially remote sensing, can help identify environmental factors associated with the occurrence of VL.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, GIS have proven to be powerful tools for analyzing the prevention and control of infectious diseases, such as malaria, tuberculosis, and human immunodefi ciency virus/acquired immunodefi ciency syndrome (HIV/AIDS) (1) .…”
mentioning
confidence: 99%